Implementation of Green Therapy in Inclusive Education at Nature Schools - Marfuah, Anisah Aah; Zulfikar, Zulfikar (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study explores the implementation of green therapy in the context of inclusive education and its impact on the well-being of students with special needs. The research method used is a qualitative case study in a nature school that implements green therapy as part of their inclusive approach. This research was conducted at Darul Istiqamah Maros Natural School. The study population consisted of students with special needs, teachers, school staff, and parents. The sampling technique used was purposive sampling, where three students with special needs were selected to participate in this study. Data collection was conducted through in-depth interviews with students, teachers, and parents; participant observation during Green Therapy activities; and document analysis related to the inclusion program and Green Therapy activities. The findings indicated that Green therapy in inclusive education positively impacts the physical, emotional, and social well-being of students with special needs, as shown by the study results. Students experienced improved social relationships with classmates, increased self-confidence, and engagement in learning. Green Therapy provided a meaningful and enjoyable learning experience for students, reflected in higher motivation and increased participation in school activities. Challenges in implementing green therapy include managing the natural environment, training teaching staff, and adapting activities to individual student needs. Collaboration between schools, parents, and experts is crucial for successful green therapy implementation in inclusive education. This study makes a valuable contribution to the development of more effective and sustainable inclusive education practices.